Problems and Challenges Faced by Womens Workers in Cashew Industry-Kandavara Panchayat, Kundapuratq, Udupi Dist. - Geetha M. (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2023)
Cashew nut processing is mainly an export oriented seasonal industry. The cashew processing industry is a Labour-intensive industry, which provides employment opportunities mainly to women among which most of them belong to socially backward condition. It is a fact that any amount received by a woman member of staff will be utilized directly for the benefit of the family unit and hence the link relating to family wellbeing is quite apparent. Cashew industry is one of the most promising industries in the area of women employment and empowerment sustainable rural development and economic development of the country. It has a greater impact on the rural economy of Udupi District. The main intension of this research paper is to analyze the various problems and challenges faced by women workers in Cashew Industries and to identify suitable measures to safeguard their work life and work environment provided by cashew industries in Udupi District. Primary data collection done in this study to analyze the problems and challenges of women employee in the cashew industry in Kandavara Panchayat, kundapuraTq.